Assessment of excavation damaged zone around roadways under dynamic pressure induced by an active mining process. (July 2015) - Wang, Hongwei; Jiang, Yaodong; Xue, Sheng; Shen, Baotang; Wang, Chen; Lv, Jinguo; Yang, Tian
Abstract: This study presents an investigation of the excavation damaged zone (EDZ) around roadways under dynamic pressure during longwall mining. Based on their geological conditions, a total of fourteen typical roadways (seven roadways under dynamic pressure, seven roadways under static pressure) in Daxing Coal Mine, Liaoning Province, China, were selected to investigate the characteristics of their EDZ under both dynamic and static pressure with Borehole Camera Detection and Nonmetallic Ultrasonic Detection techniques. The results of the investigation indicate that the EDZ width around roadways under dynamic pressure was larger than those under static pressure due to mining-induced disturbance and the effect of unstable overlying rocks in adjacent goaf. The existence of faults and other adverse geological conditions can also contribute to the expansion of EDZs. The findings were incorporated in designing a more appropriate roadway support system. If the width of EDZ is larger than the bolt length, then the employment of bolts alone will not be sufficient to maintain roadway stability. Reinforcement with cables must be added to the support system. The reason is that cables have an overhanging effect and can be anchored in the excavation influenced zone (EIZ) which is adjacent to the EDZ in stable surrounding rock masses. The installation of cables could increase the volume of stable strata participating in the support system. Highlights: The terminologies of EDZ, EIZ and Intact Zone located in sequence were presented. The EDZ in dynamic pressure roadways was larger due to the mining disturbance. The EDZ was larger due to the effect of the unstable overlying rocks in goafs. Unfavorable geological conditions could also cause the expansion of the EDZ. The cables installation make the wider stable strata participate in support system.